Ecopopulis Paradigm In Peat Land Management In Barito Kuala District - Mahyuni Mahyuni; Ismar Hamid; Muhammad Luthfi Farizan; Mona Warah; Anisa Amalia (International Journal of Politic, Public Policy and Environmental Issues, 2021)
The environmental crisis is getting worse these days, resulting in a debate about the paradigm of natural resource management to emerge. The aspiration for sustainable natural resource management is getting stronger from civil society movements and the wider community. The purpose of this research is to describe eco-populist thoughts and actions in peatland management and to strengthen the position of the eco-populist paradigm as the right paradigm in peatland management. This research is qualitative research with a case study approach, namely research conducted intensively, in detail and in-depth on a problem that is the object of research. The results of this study contribute to a fundamental-philosophical error in peatland management. Promote a sustainable perspective on peatland management based on local knowledge, reinforced by paradigmatic studies. A perspective that harmonizes ecological and human (community) interests. Not a viewpoint that ignores certain subsystems. In natural resource politics, there are at least three paradigms. First, the conservationist paradigm, which places natural resources solely for conservation. Second, the developmentalistic paradigm, which views natural resources as development assets. Third, the eco-populistic paradigm, which is a holistic perspective that humans, flora and fauna and their environment are one ecosystem. The loss of one element shakes the joints of the other component. Peat management is one of the world's highlights today. The critical issue is that climate change is linked to the destruction of peat due to unsustainable management. Until now, peatland management is still dominant with a developmentalism cum conservationist paradigm. So it is necessary to strengthen paradigmatic in sustainable peatland management.